Study of optimum conditions for Polyhydroxybutyrate production from local isolate of Bacillus cereus B - Shayma Al-Sahlany; Shayma Al-Sahlany (University of Thi-Qar Journal of Science, 2019)
The highest Polyhydroxybutyrate (PHB) production from Bacillus cereus B56 2 8 4 73 8 35 C, for 48 hours aerobically by using shaking incubator on 150 rpm / min , 2% inoculum volume, the pH value was 7, and the production media wascontent 1% glucose as carbon source and 0.25 % peptone as nitrogen source.